Genetics and pathogenesis of idiopathic scoliosis - Grauers, A. (Scoliosis Spinal Disord, 2016)
Idiopathic scoliosis (IS), the most common spinal deformity, affects otherwise healthy children and adolescents during growth. The aetiology is still unknown, although genetic factors are believed to be important. The present review corroborates the understanding of IS as a complex disease with a polygenic background. Presumably IS can be due to a spectrum of genetic risk variants, ranging from very rare or even private to very common. The most promising candidate genes are highlighted.